Kesetaraan Gender Dalam Pendidikan Islam - Muhamad Akip (STAI Bumi Silampari, 2020)
Human creation through several pregnancy processes (biological), the process of pregnancy without the touch of a man (creation of the Prophet Jesus), and without a woman and man (creation of the Prophet Adam). the rights and obligations that God has attributed as a woman. Through empirical and historical literature and systematically collected and critically analyzed through deductive-inductive methods. Basically between men and women are fair (equal) created from the same source 'alaq or a clot of blood and and from one soul, which is contained in several values ​​of Islamic education. The value of education of faith, sharia, reason and morality in Gender Islamic education is only a term and does not distinguish them from the educational process and has rights and obligations (1) Men and women as servants (2) Men and women as caliphs (3) both have promises or vows (4 ) Men and women pledged. The education system that refers to the values ​​of Islamic teachings rahmatan lil 'alamin in various aspects that reflect the values ​​of justice and equality between men and women, instill values ​​that lead to the equal rights of anti-discrimination attitudes towards certain sexes because human nature needs each other.